PENGOLAHAN LOGAM BERAT KHROM (Cr) PADA LIMBAH CAIR INDUSTRI PENYAMAKAN KULIT DENGAN PROSES KOAGULASI FLOKULASI DAN PRESIPITASI - Maria Giacinta AS; Zainus Salimin; Junaidi Junaidi (Jurnal Teknik Lingkungan, 2013)
ABSTRACTLeather tannery industry waste water treatment research by coagulation flocculation and precipitation process has been carried out. The study aims to determine the treatment process with coagulant what is most optimum in removing the heavy metal content in leather tannery waste water, which includes coagulant lime, aluminum sulfate, and ferrous sulfate, and barium chloride, coagulant concentration, and pH optimum. Jar test result available optimum pH for coagulant lime at pH 8, for aluminum sulfate at pH 6, and for ferrous sulfate at pH 8. The optimum ratio of lime is 6,4; aluminum sulfate is 0,8; and ferrous sulfate is 0,48. The optimum concentration of barium chloride after treatment with lime, aluminum sulfate, and ferrous sulfate are 0,005; 0,043; and 0,005.